Optimal resistance training parameters for improving bone mineral density in postmenopausal women: a systematic review and meta-analysis - Zhao, Fang; Su, Wenbo; Sun, Yaowei; Wang, Jing; Lu, Bin; Yun, Hezhang (Journal of orthopaedic surgery and research, 2025)
Background This meta-analysis aims to explore the effects of resistance training on bone mineral density (BMD) in postmenopausal women, specifically focusing on different training intensities, durations, frequencies, and periods, across various skeletal sites lumbar spine (LS), femoral neck (FN), total hip (TH), and trochanter (Troch). Methods We systematically searched PubMed, Embase, Web of Science, and the Cochrane Library for studies evaluating the impact of resistance training programs on BMD in postmenopausal women, covering all records up to March 2025. Two reviewers independently screened the studies, extracted data, assessed the risk of bias using the Cochrane Handbook, and performed the meta-analysis using RevMan 5.4 and Stata 18 software. Results 17 randomized controlled trials involving 690 subjects were included. The results indicate that resistance training significantly improves BMD at the LS (SMD = 0.88, 95% CI [0.21, 1.56], P = 0.01, I 2 = 91%), FN (SMD = 0.89, 95% CI [0.40, 1.39], P = 0.0004, I 2 = 87%) and TH (SMD = 0.30, 95% CI [0.10, 0.50], P = 0.003, I 2 = 25%). However, no significant effect was observed on Troch bone density (SMD = 0.23, 95% CI [-0.01, 0.47], P = 0.06, I 2 = 19%). Subgroup analysis further revealed that high-intensity training (≥ 70% 1RM) had a significant effect on the TH and FN ( P < 0.05); training three times per week significantly improved bone mineral density at the LS, FN, TH, and Troch ( P < 0.05); intervention durations of ≥ 48 weeks had a significant impact on FN and TH ( P < 0.05); and sessions lasting 40 min had a significant effect on LS ( P < 0.05). Conclusion Resistance training can beneficially influence BMD in postmenopausal women, particularly at the LS, FN, and TH. A high-intensity training regimen (≥ 70% 1RM) performed three times per week with a longer training duration may be optimal. However, significant heterogeneity among the included studies for LS and FN bone density may affect the accuracy of the pooled results, thereby limiting the generalizability of these findings. More high-quality clinical trials are needed to confirm these findings.